PECULIARITIES OF CHRONIC GASTRODUODENAL PATHOLOGY COURSE BY THE STATUS OF PERIPHERAL MICROCIRCULATION IN CHILDREN OF SCHOOL AGE - Nechitailo, Yu.N.; Nechitailo, D.Yu.; Miheeva, T.N.; Burіak О.Н. (World of Medicine and Biology, 2018)
We examined 60 children of school age who were hospitalized in the gastroenterological department with a diagnosis of uncomplicated chronic gastroduodenal pathology. All children underwent endoscopic examination of the upper gastrointestinal tract with assessment of blood supply of the mucous membrane of the stomach and duodenum; the capillaroscopy of the nail bed. During endoscopic research of the mucous membrane of the stomach and duodenum іn children with chronic hypertrophic gastritis and chronic with erosions gastroduodenitis observed a more pronounced edema of the mucosa, stasis, and the presence of hemorrhages than in patients with chronic superficial gastritis and chronic superficial gastroduodenitis that can be explained by the result of violation of blood supply of the mucous membrane of the stomach and duodenum. Children with chronic gastroduodenitishad more often symptoms of the microcirculatory disorders: abnormal capillary tortuosity, the existence of the "sladge" phenomenon,local spasm of the capillaries and slowing of blood flow, changes in the capillary, which is understandable consequence of the autonomic dysregulation, which in its turn is accompanied by the hemodynamic changes.